2013
DOI: 10.1128/aem.01641-13
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome Survey of a Multispecies and Alga-Associated Biofilm Revealed Key Elements of Bacterial-Algal Interactions in Photobioreactors

Abstract: e Photobioreactors (PBRs) are very attractive for sunlight-driven production of biofuels and capturing of anthropogenic CO 2 . One major problem associated with PBRs however, is that the bacteria usually associated with microalgae in nonaxenic cultures can lead to biofouling and thereby affect algal productivity. Here, we report on a phylogenetic, metagenome, and functional analysis of a mixed-species bacterial biofilm associated with the microalgae Chlorella vulgaris and Scenedesmus obliquus in a PBR. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(93 citation statements)
references
References 96 publications
6
84
0
3
Order By: Relevance
“…In addition to these nutrients, interactions via particular vitamins have been elucidated; for instance, eukaryotic algae are auxotrophic for vitamin B 12 (cobalamin) that can only be synthesized by prokaryotes, and studies have revealed mutualistic relationships between vitamin B 12 -dependent algae and heterotrophic bacteria [16 ,17]. On the other hand, a metagenomic survey of alga-associated biofilms has revealed that genes involved in the biosynthesis of B vitamins and those for lipases and esterases are abundant and functional, suggesting their key roles in algae-associated bacteria [18 ]. We suggest that this approach is useful to find interactions via compounds that are difficult to be detected by chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these nutrients, interactions via particular vitamins have been elucidated; for instance, eukaryotic algae are auxotrophic for vitamin B 12 (cobalamin) that can only be synthesized by prokaryotes, and studies have revealed mutualistic relationships between vitamin B 12 -dependent algae and heterotrophic bacteria [16 ,17]. On the other hand, a metagenomic survey of alga-associated biofilms has revealed that genes involved in the biosynthesis of B vitamins and those for lipases and esterases are abundant and functional, suggesting their key roles in algae-associated bacteria [18 ]. We suggest that this approach is useful to find interactions via compounds that are difficult to be detected by chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on characterising communities in multi-species photobioreactors with molecular methods and have provided valuable insights (Krohn-Molt et al 2013 andCarney et al 2014). In addition, the development of these methods for use in photobioreactors should lead to the development of specific molecular probes for rapid monitoring of the communities present in the reactors (Carney et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the first extensive metagenomic study of the bacteria present in biofilms in a PBR in which the microalgae Chlorella vulgaris and Scenedesmus obliquus were grown, Krohn-Molt et al (2013) found that the bacterial community comprised ca. 30 species.…”
Section: Abundance and Diversity Of Bacteria Associated With Microalgaementioning
confidence: 99%